Kritik Ekonomi Islam terhadap Ajaran Marxisme tentang Sistem Kepemilikan dalam Sosial Kemasyarakatan - Jalaluddin, Jalaluddin (Masoem University, 2024)
The purpose of this article is to criticize Marxist teachings about the ownership system in social society. This research is a type of library research; namely, the data and study materials used come from library sources, in the form of books, journals, magazines, newspaper articles, papers and previous research results that support the writing theme. The form of this research is descriptive-comparative-analytic. The results showed that Islam provides criticism of Karl Marx's views on the abolition of private property. the elimination of private property as a source of alienation and exploitation is contrary to human nature. Every human being born is given the right and preference to own property. Therefore, it is very unfair when these rights and preferences are abolished. In the Islamic economic system, legal ownership in asset management is divided into three groups, namely private ownership, social ownership and state ownership.